2022
DOI: 10.1108/jhti-08-2021-0214
|View full text |Cite
|
Sign up to set email alerts
|

Local food consumption values and attitude formation: the moderating effect of food neophilia and neophobia

Abstract: PurposeThe local food tourism in Pakistan is increasing rapidly, and it attracts scholars to determine the factors affecting local food tourists' buying choices. Particularly, the authors aim to investigate the role of food consumption values on predicting domestic tourists' attitude toward local food and its effect on the intention to try local food with the moderating effect of personality traits (neophobia and neophilia).Design/methodology/approachThe authors tested the study model on 250 completed response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 125 publications
2
41
0
3
Order By: Relevance
“…Previous studies found that diners who acquire positive emotional benefits perceive values such as self-esteem and interest in strengthening social bonds (Hussain et al, 2022;Soltani et al, 2020). Tey et al (2018) found that the benefit of maintaining health is associated with consumption values such as meaningful life, longevity and sense of accomplishment, whereas enlightenment is associated with happiness.…”
Section: Relationship Between Benefits Of Consuming Local Food and Lo...mentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies found that diners who acquire positive emotional benefits perceive values such as self-esteem and interest in strengthening social bonds (Hussain et al, 2022;Soltani et al, 2020). Tey et al (2018) found that the benefit of maintaining health is associated with consumption values such as meaningful life, longevity and sense of accomplishment, whereas enlightenment is associated with happiness.…”
Section: Relationship Between Benefits Of Consuming Local Food and Lo...mentioning
confidence: 99%
“…Perceived local food benefits can lead to consumption values because tourists assess utility from food consumption based on the benefits derived (Soltani et al , 2020). Through tasting local food, tourists can derive emotional benefits including satisfaction, pleasure, relaxation and excitement (Hussain et al , 2022; Baah et al , 2019). Also, they can seek epistemic benefits such as the discovery of novel local food, understanding a new culture and experiencing different food tastes (Badu-Baiden et al , 2022; Correia et al , 2020).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…While existing literature provides an understanding on how food-related personality traits affect various aspects on the behaviour of travellers, there is an evident gap of knowledge in the ways food-related personality traits affect perceptions of a gastronomic destination image (Chang and Mak, 2018; Hsu and Scott, 2020; Hussain et al , 2022). In addition, the current tourism research predominantly uses linear examination for the themes under evaluation (Pappas and Glyptou, 2021).…”
Section: Introductionmentioning
confidence: 99%